Involvement of Descending Serotonergic and Noradrenergic Systems and their Spinal Receptor Subtypes in the Antinociceptive Effect of Dipyrone - Gencer, A.; Gunduz, O.; Ulugol, A. (Drug Research, 2015)
The antinociceptive effect of dipyrone is partly due to its action upon pain-related central nervous system structures. Despite intensive research, the precise mechanisms mediating its analgesic effects remain unclear. Here, we aimed to determine whether neurotoxic destruction of descending inhibitory pathways affect dipyrone-induced antinociception and whether various spinal serotonergic and adrenergic receptors are involved in this antinociception. The nociceptive response was assessed by the tail-flick test. Mice injected with dipyrone (150, 300, 600 mg/kg, i.p.) elicited dose-related antinociception. The neurotoxins 5,7-dihydroxytryptamine (50 μg/mouse) and 6-hydroxydopamine (20 μg/mouse) are applied intrathecally to deplete serotonin and noradrenaline in the spinal cord. 3 days after neurotoxin injections, a significant reduction in the antinociceptive effect of dipyrone was observed. Intrathecal administration of monoaminergic antagonists (10 μg/mouse), the 5-HT2a antagonist ketanserin, the 5-HT3 antagonist ondansetron, the 5-HT7 antagonist SB-258719, α1-adrenoceptor antagonist prazosin, α2-adrenoceptor antagonist yohimbine, and the β-adrenoceptor antagonist propranolol also attenuated dipyrone antinociception. We propose that descending serotonergic and noradrenergic pathways play pivotal role in dipyrone-induced antinociception and spinal 5-HT2a, 5-HT3, and 5-HT7-serotonergic and α1, α2, and β-adrenergic receptors mediate this effect.
Keywords: antinociception; descending inhibition; dipyrone; noradrenergic system; serotonergic system